Lingkungan di Panti Werdha Yang Mendukung Kualitas Tidur Baik Pada Lanjut Usia - Prabasari, Ninda Ayu; Manungkalit, Maria; Radjawane, Cormutia Jesica (JURNAL NERS LENTERA, 2022)
Sleep needs at each stage are different. When you get older, there are changes in sleep patterns that cause the sleep quality of the elderly to change. One of the changes that occur is due to individual environmental factors. The purpose of this study was to describe the nursing home environment that supports good sleep quality in the elderly. The research method is descriptive research design. The study population was all elderly people aged > 60 years at the Surya Panti Surya Surabaya's Elderly House. The research sample amounted to 45 respondents with purposive sampling technique. The variables of this study were the nursing home environment and sleep quality. Sleep quality was measured by the Pittsburgh Sleep Quality Index (PSQI) questionnaire, and the environment was given a questionnaire and observation sheets. The results of this study showed that 45 respondents (100%) had good sleep quality with the majority of respondents choosing a bright light parlor environment as many as 16 respondents (36%) with a normal room temperature as many as 29 respondents (65%), no noise level as many as 30 respondents (67%). The elderly who live in orphanages have different habits of room environmental conditions (light and temperature) when the elderly sleep and the elderly already have good adaptation to the environment so that the quality of sleep can be maintained properly.